The practical indications for implementation of quality assurance program in radiotherapy – procedures - Kierzkowski, Jerzy; Kubicka, Maria; Bogusz-Osawa, Marta (Contemporary Oncology/Współczesna Onkologia, 2002)
Quality Assurance in health care has become more and more important in recent years. In Poland, the Government and the National Atomic Energy Agency had decided that hospitals treating patients with radiotherapy have to develop quality assurance programs and they will be held responsible for quality control within their institutions. Therefore managers of hospitals have started paying more attention to planned and systematic actions necessary for providing medical services that will meet all quality standards. However the high quality of medical services can be accomplished only by highly rationalized, integrated and well organized actions, built on the fundamentals of common sense and logics. The actions become standardized and reliable, which decreases the number of errors or malfunctions. The possibility of providing the desirable products to patients also increases. Only the logical and efficient management of the hospital, concentrating on patients and their current and future needs is capable of delivering full medical services , that fulfill the patient's requirements and wishes. Therefore focusing on the organizational structure, the work systematization within departments taking part in radiotherapy, and personnel training should be the main tasks in the quality assurance program. The aim of this article is to present the practical solutions for implementing the Quality Assurance Program in radiotherapy departments. It provides information on how to develop the QA program referring to aspects such as legal documentation (including standards and procedures) infrastructure of the department, work organization, qualification and education of the personnel, the process of providing medical services and other factors which have been neglected so far.